Hospitalization in maintenance peritoneal dialysis: a review. Issue 1 (1st January 2023) - Vogt, Braden; Painter, David F; Saad Berreta, Rodrigo; Lokhande, Anagha; Shah, Ankur D
ABSTRACT: Although hemodialysis continues to be the dominant form of dialysis in the United States, peritoneal dialysis rates continue to rise both nationally and worldwide. Peritoneal dialysis offers patients increased flexibility due to the ability to dialyze at home, leading to potential quality of life benefits for patients. However, questions exist regarding clinical outcomes in patients on peritoneal dialysis and the literature has not recently been reviewed. This review examines hospitalizations within patients utilizing peritoneal dialysis, including comparison to other dialysis modalities. Much heterogeneity exists within the literature, often explained by patient population. Recent data show all-cause, cardiovascular, and infection-related hospitalizations to be high in patients on peritoneal dialysis, although data variation limits conclusions in comparison to other modalities. This review found there is insufficient evidence to suggest admission rates are different in peritoneal dialysis than in-center hemodialysis. While the rate is similar to infectious causes, most studies report cardiovascular complications to be the leading cause of hospitalization. Some evidence suggests that cardiovascular hospitalizations occur at a higher rate in peritoneal dialysis, but further studies are required. The infection-related hospitalization rate appears to be higher in peritoneal dialysis due to rates of peritonitis, but rates of life-threatening bacteremia are lower. Differences in reporting of hospital days vs. length of stay challenge the interpretability of length of stay data between modalities, but patients on PD may spend more days per year in the hospital. In summary, hospitalization is highly prevalent in patients on peritoneal dialysis and few definitive conclusions can be drawn in comparison to other dialysis modalities. In eligible patient populations who desire increased flexibility, peritoneal dialysis is a reasonable modality choice.